Systemic therapy in the management of recurrent or metastatic salivary duct carcinoma: A systematic review. (September 2020) - Uijen, M.J.M.; Lassche, G.; van Engen-van Grunsven, A.C.H.; Tada, Y.; Verhaegh, G.W.; Schalken, J.A.; Driessen, C.M.L.; van Herpen, C.M.L.
Highlights: Salivary duct carcinoma often requires palliative systemic therapy. Currently no guidelines exist on systemic therapy for this rare cancer. This paper summarizes the evidence of different palliative treatment strategies. It is recommended to test the AR and HER2 status of salivary duct carcinomas. Agents targeting the AR or HER2 pathways are the cornerstone for systemic therapy. Abstract: Background: Salivary duct carcinoma (SDC) is an aggressive subtype of salivary gland cancer. Approximately half of SDC patients will develop recurrences or metastases. Therapeutic palliative therapy is therefore often needed. The majority of SDC tumors expresses the androgen receptor (AR) and one-third expresses human epidermal growth factor receptor 2 (HER2), both are potential therapeutic targets. The aim of this paper is to systematically review and summarize the evidence on systemic palliative therapy for SDC and to provide treatment recommendations. Materials and methods: Electronic libraries were systematically searched with a broad search strategy to identify studies where SDC patients received systemic therapy. Due to the rarity of SDC no restrictions were placed on study designs. Results: The search resulted in 2014 articles of which 153 were full-text analyzed. Forty-five studies were included in the analysis, which included in total 256 SDC patients receiving systemic therapy. Two phase 2 trials primarily including SDC patients were identified. The majority of the studies were case series or case reports, resulting in an overall low quality of available evidence. Based on studies including ≥ 5 SDC patients, objective responses to HER2 targeting agents were observed in 60–70%, to AR pathway agents in 18–53% and to chemotherapy in 10–50%. Conclusion: For AR or HER2 positive SDC, agents targeting these pathways are the cornerstone for palliative treatment. Regarding chemotherapy, the combination of carboplatin combined with a taxane is best studied. Regarding other targeted agents and immunotherapy evidence is anecdotal, limiting formulation of treatment recommendations for these antineoplastic agents.